Research of composition and photocatalytic property of carbon-doped Ti-O films prepared by R-MS using CO2 gas resource - Wen, F.; Zhang, C.; Xie, D.; Sun, Hongqi; Leng, Y. (Elsevier, 2013)
In this paper, carbon-doped Ti-O films were prepared on silicon wafer and stainless steel by reaction magnetron sputtering using CO 2 as carbon and oxygen source. By changing the ratio of CO 2 /O 2 , a series of films with different composition can be obtained. X-ray photoelectron spectroscopy (XPS) was employed to analyze composition of as-prepared films. The result proved that carbon was doped into titanium successfully. Ultraviolet-visible (UV-Vis) spectrophotometer in the wavelength range of 250- 900 nm was used to record the absorbance of as-prepared film samples. The photocatalytic activities of as-prepared films were evaluated by measuring the decolorization rate of methyl orange under UV light irradiation. The results showed that as-prepared carbon-doped Ti-O films have fairly photocatalysis activity, which to be hoped to become candidate materials for photocatalyst. © 2013 Elsevier B.V. All rights reserved.